#### Answer

x = 1
y = -3

#### Work Step by Step

simplify to first equation-5y + 6y = 3x + 2 ( x - 5 ) -3x + 5
y = 3x + 2x - 10 - 3x + 5
y = 2x -5
simplify to second equation 4 ( x + y ) -x + y = -12
4x + 4y -x + y = -12
3x + 5y = -12 here substitude y = 2x - 5
3x + 5 ( 2x - 5 ) = -12
3x + 10x -25 = -12 use the distributive property
13x -25 = -12 simplify
13x = -12 + 25
13x = 13 divide both sides by 13
$\frac{13x}{13}$ = $\frac{13}{13}$
x = 1
substitude x =1 to y = 2x - 5
y = $2\times1$ - 5
y = 2 - 5
y = -3